Role of Personalized Learning Program by Learning Management System in Higher Education in Binus Bandung Indonesia - Agus Masrukhin (Engineering Proceedings)
This study aims to provide an overview of the effectiveness and responsiveness of the personalized learning model in terms of Industry 4.0. A qualitative and descriptive research method was used as students, staff, and lecturers were interviewed. Campus and journal practices were examined, and peer-reviewed articles in multiple journals, including publications, personal study lectures, and learning analysis, were analyzed. The paradigm shift in curriculum development and personalized learning design, with the help of the learning management system, helped students become more independent and effective in learning.